Disturbances in the FGFR1-5-HT1A Heteroreceptor Complexes in the Raphe-Hippocampal 5-HT System Develop in a Genetic Rat Model of Depression - Borroto-Escuela, Dasiel O.; DuPont, Caitlin M.; Li, Xiang; Savelli, David; Lattanzi, Davide; Srivastava, Ipsit; Narváez, Manuel; Di Palma, Michael; Barbieri, Elisa; Andrade-Talavera, Yuniesky; Cuppini, Riccardo; Odagaki, Yuji; et al. (Frontiers in Cellular Neuroscience, 2017)
The FGFR1-5-HT1A heteroreceptor complexes are involved in neuroplasticity in the rat hippocampus and in the mesencephalic raphe 5-HT nerve cells. There exists a 5-HT1A protomer enhancement of FGFR1 protomer signalling. Acute and ten day treatment with i.c.v. FGF-2 and the 5-HT1A agonist 8-OH-DPAT produced enhanced antidepressant effects in the forced swim test. We studied in the current work the disturbances in the FGFR1-5-HT1A heterocomplexes in a genetic rat model of depression, the Flinders sensitive line rats (FSL) of Sprague-Dawley (SD) origin, by means of neurochemical, neurophysiological and behavioral techniques. In control SD rats, the FGFR1 agonist SUN11602 and FGF2 produced a significant reduction of GIRK currents induced by 8-OH-DPAT in the CA1 area of the hippocampus. In FSL rats, only i.c.v. 8-OH-DPAT alone treatment produced a significant reduction in the immobility time. The combined i.c.v. treatment (FGF2 + 8-OH-DPAT) in FSL rats did not cause a significant decrease in immobility time in the forced swim test. However, in the SD rats this combined treatment produced a significant reduction. Furthermore, in the FSL rat a significant increase in the density of FGFR1-5-HT1A proximity ligation assay (PLA) positive clusters was only found after i.c.v. 8-OH-DPAT treatment alone in the CA2 and CA3 areas. In the SD rat a significant increase in the density of specific PLA clusters was only observed in the CA2 area of the i.c.v. combined treatment (FGF2 + 8-OH-DPAT) group. No treatment led to significant changes in the PLA clusters of the dorsal raphe in the FSL rat. However, significant changes in the density of specific PLA clusters were only found in the dorsal raphe of SD rats after combined treatment and treatment with 8-OH-DPAT alone. The results indicate that in FSL rats compared with SD rats alterations may develop in the ability of 8-OH-DPAT and combined FGFR1 and 5-HT1A agonist treatment to increase the density of FGFR1-5-HT1A heteroreceptor complexes of the dorsal raphe. It is proposed that such deficits in FSL rats may possibly reflect a failure of the combined agonist treatment to uncouple the 5-HT1A autoreceptors from the GIRK channels.